Privata skogsägares kunskap om dikning på skogsmark - Hedlund, John (2017)
The purpose of this study is to investigate how good knowledge private forest owners have about draining forest land. The method used was a survey with questions on contemporary methods. The questionnaire was sent out to 50 forest owners.